What People Search for When Browsing "Doctor Google." An Analysis of Search Trends in Italy after the Law on Pain. (2nd January 2021) - Miceli, Luca; Bednarova, Rym; Bednarova, Iliana; Rizzardo, Alessandro; Cobianchi, Lorenzo; Dal Mas, Francesca; Biancuzzi, Helena; Bove, Tiziana; Dal Moro, Fabrizio; Zattoni, Fabio
Abstract: Italy adopted a law on chronic pain in March 2010, which focused on detection and management of this symptom, that affects approximately 25% of the population. The aim of this study is to analyze the interest of the Italian population in palliative care and chronic pain and to understand whether the Law 38/2010 made an impact on the internet search on chronic pain. Five research parameters were included using Google Trends (chronic pain, anti-inflammatory drugs, opioids, fibromyalgia, medical cannabis) from 2004 to 2019 using "joint point regression analysis." Comparisons of annual relative search volume (ARSV), average annual percentage change (AAPC), and temporal patterns were analyzed to assess loss or gain of interest in research of all the terms after adopting Law 38/2010; collected data were analyzed using Kruskall-Wallis test. The research trend of almost every word increased in time (AAPC > 0) with significant inflexion points after issuing law on chronic pain management in March 2010. Our results suggest the relevance of internet search engines, like "Doctor Google, " to translate and share knowledge about specific conditions, diseases, and treatment alternatives, with a call to a raise in authoritative scientific voices on the topic, especially when it comes to widespread conditions like chronic pains.